Qualification and quantification of bacterial pathogen load in acute bovine respiratory disease cases. - Roof, Clinton (Kansas State University, 2011)
One hundred ninety four steers, bulls, and heifers weighing 182-318 kg were purchased at an Arkansas sale barn and shipped 12 hours to a northern Kansas feedlot. There was no previous history of treatment and the cattle had been delivered to the sale barn within the 24 hour period prior to the sale. The objectives of the study were to evaluate (1) bacterial pathogen isolates in different locations in the respiratory tract, (2) pathogen load in clinically ill and clinically normal calves, and (3) compare histological damage that may be a result of clinical disease. Fifteen calves were identified with signs of acute bovine respiratory disease (BRD) based on clinical score and a minimum rectal temperature of 40° C. An additional 5 calves with no clinical signs and rectal temperatures < 40° C were selected as controls. Cattle were humanely euthanized following recording of antemortem clinical observations. At postmortem, samples for microbiologic and histologic (hematoxylin and eosin stain) analysis were collected from grossly normal and/or consolidated tissue in each lung lobe. Samples were also collected from the tonsils and trachea. Quantification of the BRD pathogens per gram were determined for each positive site and then converted to total counts for each animal. Total colony forming units (CFU) of pathogens in the entire lung for cattle with identified pathogens ranged from 2x10[superscript]7 – 2x10[superscript]8 CFU for Pasturella multocida and 9x10[superscript]6 – 9x10[superscript]8 CFU for Mannheimmia haemolytica. Total visual estimated percent consolidation ranged from 0.0% to 45.0% of the total lung. Isolated pathogens from the upper and lower respiratory tract were compared and showed to have no significant agreement. Histology scores of 0-4 were assigned to the tissue samples and compared to the quantified BRD pathogens to test a possible association between the pathologic process and the total agents in that tissue sample. A significant difference in bacterial counts between histology scores of zero or 1 and a histology score of 4 was observed.
Keywords: Bovine Respiratory Disease; Acute; Qualification; Quantification; Pathogen Load; Animal Sciences (0475); Veterinary Medicine (0778)